Dynamic mechanisms of land use spatial conflicts in mining cities: A case study of Xintai City, China - Yang Zheng; Kao Wang; Runmei Hao (Resources, Environment and Sustainability)
With resource extraction and transformational development, the hindering effect of land use spatial conflict (LUSC) on mining city development is significant, highlighting the importance of exploring the dynamic mechanism of LUSC for sustainable development. This study integrates the multidimensional attributes of LUSC, constructs a LUSC assessment framework based on “element- pattern-effect”, and proposes theoretical hypotheses on the dynamic mechanism of LUSC. Taking Xintai City, a typical mining city in China, as an example, we analyzed the characteristics of LUSC evolution from 2000 to 2020 and explored the impact mechanism of LUSC by using the SEM model. Results show that the high risk of LUSC in mining cities is clustered in mining-city intertwined zones, and the growth rate of LUSC risk increases significantly with the transition period. The dynamic mechanisms of LUSC in mining cities are mutually driven by natural and anthropogenic factors and are dominated by anthropogenic factors. On the impact pathway, ecological environment, socio-economic environment, and resource extraction have stable and significant direct effects on LUSC. With improvements in technology and policy, the constraints on land use imposed by the natural environment have gradually decreased, and the impacts on LUSC are mostly indirect. This study proposes a research framework for the dynamic mechanism of LUSC in mining cities to provide theoretical guidance and suggestions for promoting urban transformation and development.